2021
DOI: 10.1002/jcu.23009
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between left atrial volumes and strains in healthy adults: Detailed analysis from the three‐dimensional speckle‐tracking echocardiographic MAGYAR‐Healthy Study

Abstract: Introduction:Little is known about the relationship between left atrium (LA) volumes and contractility features along the cardiac cycle. The present study aimed to assess, by threedimensional speckle-tracking echocardiography (3DSTE), correlations between LA volumes, volume-based functional properties, and strains during the cardiac cycle in healthy adults.Methods: We included 217 healthy adult volunteers (mean age 33.4 ± 12.7 years, 112 males) who underwent complete two-dimensional Doppler echocardiography wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…In a recent study, similar LA analysis was performed in healthy subjects by 3DSTE ( 3 ). Compared to these findings, RA functional properties showed different patterns with increasing RA volumes as compared to findings with LA ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study, similar LA analysis was performed in healthy subjects by 3DSTE ( 3 ). Compared to these findings, RA functional properties showed different patterns with increasing RA volumes as compared to findings with LA ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, similar LA analysis was performed in healthy subjects by 3DSTE ( 3 ). Compared to these findings, RA functional properties showed different patterns with increasing RA volumes as compared to findings with LA ( 3 ). While atrial volumes and stroke volumes showed similar increase with increasing atrial volumes, emptying fractions in reservoir and booster pump functions remained unchanged for both atria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations